Dare la parola ao mondo - Paulo Freire e Augusto Boal - IPF, Instituto Paulo Freire; Baena, Bernardo; Biaggioni, Leticia; Enrique, Hayala; Freire, Lutgardes Costa; Rosenberg, Marta; Scatolini, Roberta (Instituto Paulo Freire, IPF, 2021)
Depoimento da profa. Roberta Scatolini, educadora do Instituto Paulo Freire (IPF), sobre como Paulo Freire, com sua "Pedagogia do Oprimido", e Augusto Boal, com seu "Teatro do Oprimido", influenciam seu trabalho e prática educativa; sobre o sentido da palavra "opressão" e quais os mecanismos de opressão, hoje, no Brasil. An interview with teacher Roberta Scatolini, from Instituto Paulo Freire (IPF - São Paulo/Brazil), about how Paulo Freire, with his "Pedagogy of the Oppressed", and Augusto Boal, with his "Theatre of the Oppressed", have influenced her work and educational practice. She said also about the meaning of the word "oppression", and what are the mechanisms of oppression today in Brazil.